Classification and clinical features of adverse drug reactions in patients with ulcerative colitis treated with 5‐aminosalicylate acid: a single-center, observational study. (1st February 2022) - Tsujii, Yuri; Nishida, Tsutomu; Osugi, Naoto; Fujii, Yoshifumi; Sugimoto, Aya; Nakamatsu, Dai; Mukai, Kaori; Matsumoto, Kengo; Hayashi, Shiro; Yamamoto, Masashi; Nakajima, Sachiko
Abstract: Background: 5-Aminosalicylate acid (5-ASA) is a crucial drug for ulcerative colitis (UC) patients. 5-ASA has several side effects. However, the types of side effects vary and are sometimes severe. Methods: A single-center, retrospective cohort study was conducted from September 2001 to June 2020. We surveyed consecutive UC patients who visited our hospital and investigated adverse drug reactions (ADRs) related to 5-ASA formulations. We grouped patients into four subgroups: (1) lupus-like symptoms, (2) blood test abnormalities, (3) mimicking IBD exacerbation and (4) others. Their clinical courses were evaluated. Results: We surveyed 288 consecutive UC patients, 35 of whom developed ADRs of any grade (12.9%), and analyzed 27 patients. The median age and 5-ASA doses were 43 years and 4000 mg, respectively, and 48% were male. The ADR triggers were the first use of 5-ASA ( n  = 17, 63%), 5-ASA switch ( n  = 9, 33%) and 5-ASA dose escalation ( n  = 1, 3.7%). The median time to ADR was 15 days (IQR: 7, 63). Ten patients (37%) had grade 3/4 ADRs. Fever was the most common ADR ( n  = 6, 23%), followed by hyperamylasemia and headache ( n  = 4, 15%). Lupus-like symptoms accounted for 56% ( n  = 15), blood test abnormalities for 26% ( n  = 7), mimicking IBD exacerbation for 15% ( n  = 4) and others for 3.7% ( n  = 1). The time to ADR was shorter in the mimicking IBD exacerbation group (median 11 days) than in the lupus-like symptoms (22 days) and blood test abnormalities (55 days) groups. Conclusion: Classification of ADRs related to 5-ASA into four groups might lead to early recognition of ADRs.